2019
DOI: 10.1002/maco.201810620
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric corrosion of zinc in coastal atmospheres

Abstract: The atmospheric corrosion of zinc in pure marine coastal atmospheres has not been extensively studied. This paper presents the results obtained in six pure marine atmospheres located at different distances from the seashore in the same coastal area with annual chloride deposition rates of between 47 and 1142 mg · m−2 · day−1. Zinc specimens were exposed for 3, 6, 9, and 12 months in two annual exposure sequences starting 6 months apart. Tests were performed to determine the corrosion rate and its evolution wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 30 publications
3
15
0
Order By: Relevance
“…SEM, scanning electron microscopy Numerous investigations have reported the characterization of the corrosion products on galvanized steel upon exposure to the atmosphere. [14,[39][40][41] The present study agreed well with the findings of other studies where morphologies usually found were platelets or hexagonal type or spherically aggregated simonkolleite, needle-like structure, or flatten the dark surface of hydrozincite. [14,[39][40][41] 3.5.2 | FTIR spectroscopy Figure 9 shows infrared spectra and Table 5 depicts the FTIR characteristic bands of the corrosion products formed on galvanized steel exposed at the urban, industrial, and marine test sites located in Karachi coastal city.…”
Section: Scanning Electron Microscopy/ Energy-dispersive X-ray Specsupporting
confidence: 92%
See 2 more Smart Citations
“…SEM, scanning electron microscopy Numerous investigations have reported the characterization of the corrosion products on galvanized steel upon exposure to the atmosphere. [14,[39][40][41] The present study agreed well with the findings of other studies where morphologies usually found were platelets or hexagonal type or spherically aggregated simonkolleite, needle-like structure, or flatten the dark surface of hydrozincite. [14,[39][40][41] 3.5.2 | FTIR spectroscopy Figure 9 shows infrared spectra and Table 5 depicts the FTIR characteristic bands of the corrosion products formed on galvanized steel exposed at the urban, industrial, and marine test sites located in Karachi coastal city.…”
Section: Scanning Electron Microscopy/ Energy-dispersive X-ray Specsupporting
confidence: 92%
“…[14,[39][40][41] The present study agreed well with the findings of other studies where morphologies usually found were platelets or hexagonal type or spherically aggregated simonkolleite, needle-like structure, or flatten the dark surface of hydrozincite. [14,[39][40][41] 3.5.2 | FTIR spectroscopy Figure 9 shows infrared spectra and Table 5 depicts the FTIR characteristic bands of the corrosion products formed on galvanized steel exposed at the urban, industrial, and marine test sites located in Karachi coastal city. It was found that the corrosion products formed on galvanized steel exposed at all the test sites were F I G U R E 7 SEM images of the galvanized steel after 12 months of exposure at the industrial (T 6 and T 7 ) and marine test sites (T 8 -T 10 ) located in Karachi coastal city.…”
Section: Scanning Electron Microscopy/ Energy-dispersive X-ray Specsupporting
confidence: 92%
See 1 more Smart Citation
“…This causes the deposition of a Zn layer on top of the steel alongside several Fe–Zn intermetallic layers which create a protective barrier from the environment . The Zn layer itself is corrodible by ambient air, creating several corrosion products depending on the environment of the workpiece limiting the coatings life time . These corrosion products, on the contrary, can also contribute to the corrosion protection in particular if they are forming insoluble products that have a large volume and may reduce access of water and oxygen to the plane surface or into scratches.…”
Section: Introductionmentioning
confidence: 99%
“…These corrosion products, on the contrary, can also contribute to the corrosion protection in particular if they are forming insoluble products that have a large volume and may reduce access of water and oxygen to the plane surface or into scratches. Such products can be zinc carbonate, hydrozincite, akaganeite, or simonkolleite …”
Section: Introductionmentioning
confidence: 99%